Analysis of the Impact of Moisture and Biodeterioration on the Assessment of the Technical Condition of Historical Buildings - Ksit, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper deals with issues related to the diagnosis of dampness and mycological tests in historic buildings. The selection of appropriate diagnostic procedures in the case of historic buildings undergoing modernisation, revitalisation or renovation is an important element of properly conducted works aimed at the preservation of cultural heritage.
Keywords: moisture testing; mycological testing; expertise; historic building